2016
DOI: 10.1212/wnl.0000000000002305
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioral screening reveals prevalent impairment in a large multicenter ALS cohort

Abstract: This investigation revealed high levels of cognitive and behavioral impairment in patients with ALS within 18 months of symptom onset, comparable to prior investigations. This investigation illustrates the successful use and scientific value of adding a cognitive-behavioral screening tool in studies of motor neuron diseases, to provide neurologists with an efficient method to measure these common deficits and to understand how they relate to key clinical variables, when extensive neuropsychological examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 35 publications
3
52
1
1
Order By: Relevance
“…In our earlier report, we did find associations among depressive symptoms, measures of distress, and wish to die. 6 However, of the 62 patients who expressed a wish to die in this study, only 23 (37%) were clinically depressed. This may account for the apparent inconsistency in the current study of finding an association between depression and behavioral impairment, but no association between behavioral impairment and wish to die.…”
Section: Methods Research Questionsmentioning
confidence: 58%
See 1 more Smart Citation
“…In our earlier report, we did find associations among depressive symptoms, measures of distress, and wish to die. 6 However, of the 62 patients who expressed a wish to die in this study, only 23 (37%) were clinically depressed. This may account for the apparent inconsistency in the current study of finding an association between depression and behavioral impairment, but no association between behavioral impairment and wish to die.…”
Section: Methods Research Questionsmentioning
confidence: 58%
“…Results from the cognitive and psychiatric/psychosocial baseline data of COSMOS, 6,7 previously published separately, are integrated in the current analysis. We 6 had found that 60% of patients had mild to moderate executive functioning impairment on a short screening battery, somewhat higher than reported elsewhere, [8][9][10] while on behavioral measures (emotional-interpersonal function), 30% had mild or moderate impairment, 5 consistent with other reports. 8,11 Of 247 patients with complete data on the ALS-Cognitive Behavioral Screen (CBS), 50 (20%) showed impairment on both cognitive and behavioral measures.…”
mentioning
confidence: 99%
“…With such screening tools, the incidence of the cognitive impairment in ALS ranges from 30 to 75% [20][21][22][23] and the rate of behavioral impairment ranges from 14%…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…eases, characterized by the progressive degeneration of upper motor neurons (UMNs) and lower motor neurons (LMNs), in association with bulbar and pyramidal signs [1] [2] [3]. The involvement of these neurons results in several symptoms such as respiratory difficulties and dysphagia, as well as physical and cognitive deficits [4] [5] [6].…”
mentioning
confidence: 99%
“…Cognitive changes can occur in 35% -50% of ALS patients, which consequently lead to a spectrum of functional and behavioral deficiencies that directly influence a patient's planning and decision-making capacity. In more recent literature, ALS is recognized as a multisystemic disease that may be associated with varying degrees of cognitive and behavioral dysfunction [3] [16] [17] [18].…”
mentioning
confidence: 99%